2017
DOI: 10.1021/jacs.7b04695
|View full text |Cite
|
Sign up to set email alerts
|

A Mononuclear Nonheme Iron(V)-Imido Complex

Abstract: Mononuclear nonheme iron(V)-oxo complexes have been reported previously. Herein, we report the first example of a mononuclear nonheme iron(V)-imido complex bearing a tetraamido macrocyclic ligand (TAML), [(TAML)FeV(NTs)]− (1). The spectroscopic characterization of 1 revealed an S = 1/2 Fe(V) oxidation state, an Fe—N bond length of 1.65(4) Å, and an Fe—N vibration at 817 cm−1. The reactivity of 1 was demonstrated in C—H bond functionalization and nitrene transfer reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
84
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 37 publications
1
84
0
Order By: Relevance
“…Therefore, dihydroheteroanthracenes are often assumed to be suitable model substrates to test for basic C−H amination activity, even for relatively non‐reactive nitrene intermediates . Especially xanthene is a commonly used substrate to investigate reaction kinetics of such reactions …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, dihydroheteroanthracenes are often assumed to be suitable model substrates to test for basic C−H amination activity, even for relatively non‐reactive nitrene intermediates . Especially xanthene is a commonly used substrate to investigate reaction kinetics of such reactions …”
Section: Introductionmentioning
confidence: 99%
“…[25,26] Our group is interested in the formation and characterization of new metal-nitrene complexes from known nitrenep recursors and ideally directly from primarya mines.A so thers, we adopted the reasoning that successful nitrene transfer could be dictated by the relative bond dissociation free energy (BDFE) of the CÀHb ond, with al ower BDFE expectedly resulting in faster nitrene insertion. [25,[27][28][29][30][31][32][33] Dihydroheteroanthracenes (xanthene,t hioxanthene, and dihydroacridine derivatives) have low CÀHb ond dissociation energies (BDE) in the range of 74-81 kcal mol À1 . [34] Therefore, dihydroheteroanthracenes are often assumedt ob es uitable model substrates to test forb asic CÀH amination activity,even for relativelynon-reactive nitrene intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, unlike the iron(IV and V)-oxo systems, most of the synthetic iron-imido complexes reported so far are limited to iron(IV)-imido complexes, 5 and a mononuclear iron(V)-imido complex bearing a highly negatively charged TAML, [Fe V (NTs)(TAML)] − ( 1 ), was successfully synthesized by some of us very recently. 6 Encouraged by the successful synthesis of 1 , we attempted to oxidize it further to obtain a species such as [Fe VI (NTs)-(TAML)]. Interestingly, we observed that the iron(V)-imido complex was oxidized at the TAML site, but not at the iron center.…”
mentioning
confidence: 99%
“…Titration experiments, monitored at 750 nm as a function of the amount of [Ru(bpy) 3 ] 3+ added (Figure 1a, inset), indicated that the complete conversion of 1 to 2 required a stoichiometric amount of the [Ru(bpy) 3 ] 3+ oxidant. While the X-band EPR spectrum of 1 exhibited an isotropic signal at g = 2.00, 6 2 is EPR silent (SI, Figure S3). The latter result suggests that (i) a low-spin ( S = 1/2) iron(V) in 1 was oxidized to iron(VI) ( S = 0) or (ii) a one-electron oxidized TAML was antiferromagnetically or ferromagnetically coupled with ( S = 1/2) iron(V) (vide infra).…”
mentioning
confidence: 99%
See 1 more Smart Citation